Family member opioid prescriptions and opioid use disorder. (August 2019) - Ali, Mir M.; Henke, Rachel Mosher; Mutter, Ryan; O'Brien, Peggy L.; Cutler, Eli; Mazer-Amirshahi, Maryann; Pines, Jesse M.
Abstract: It is recognized that family members are a major source of diverted opioids. Yet it is not known how family member opioid prescriptions predict the development of an opioid use disorder (OUD).We conducted an observational study using commercial health care claims to investigate the association between a family member opioid prescription and an individual having an OUD-related claim in a large sample of patients with commercial insurance. We found that individuals had higher odds of having an OUD when a family member had an opioid prescription. This effect was magnified in spouses and employees compared with adolescents and young adult dependents. In addition, adult dependents with a pre-existing non-OUD substance use disorder had higher odds of having an OUD when a family member also had an opioid prescription. Given the high risk of opioid-related morbidity and mortality, more attention should be given to safeguard opioid diversion and to facilitate appropriate disposal of unused opioids. Highlights: Having a family member with an opioid Rx increased odds of opioid addiction. Effect was greater in spouses and employees than in adolescents. Effect was greater in adults with pre-existing non-OUD substance use disorder.